Optimizing Vendor Selection and Standardization in EDC Machine Supply Chain - Aditya Purwanto; Heru Purnomo Ipung; Eka Budiarto (Jurnal Penelitian Pendidikan IPA, 2025)
The main problems faced by the organization are undelivered SLA performance, non-standard quality between vendors in different areas nationally, and no standard in outsourcing of certain selected vendors. This study aims to optimize the vendor selection and standardization process in the EDC machine supply chain process at PT. XYZ, by utilizing the IT Governance approach using COBIT 2019. By using a research methodology with qualitative and quantitative approaches, this study analyzes the gap between Vendor Governance by utilizing the main domains of COBIT 2019, especially in APO10 (Managed Vendors), DSS01 (Managed Operations), and MEA01 (Monitoring Performance). This process includes mapping Enterprise Goal to Alignment Goal and selecting the relevance domain to be used, and measuring the process Capability Level using Level 0-5. The results of the study show that more of several key activities in the APO10, DSS01 and MEA01 domains are still at capability levels 2 and 3, indicating that some activities are not well documented consistently in some areas. Therefore, the novelty of this research is conveyed by making a performance assessment based on Simple Weighted Average (SAW) as part of the Multi Criteria Decision Making (MCDM) model, performance scorecard, vendor evaluation and vendor rationalization simulation to enforce efficiency and improve service quality.